Emergence of T4SS-type-ICE-carrying emm28 Streptococcus pyogenes causing invasive infection in Shanghai, China - Qiong Wu; Yue Jiang; PanPan Lv; Mingliang Chen (Journal of Global Antimicrobial Resistance)
Objective: Invasive group A streptococcal (iGAS) infections have been increasing in Europe, Australia, and the USA, but few data from China are available. This study intended to provide local data to highlight the characteristics of iGAS infections in China. Methods: A retrospective analysis was performed on clinical iGAS infection data from 2014 to 2023 in a tertiary hospital in Shanghai, China. Genomic analysis was conducted to characterize antimicrobial resistance, virulence, prophages, and integrative and conjugative elements (ICEs), as well as phylogenetic clusters. Results: From 2014 to 2023, a total of 21 iGAS cases were discovered, with soft tissue infections accounting for 61.9% (13/21) and 85.7% (18/21) of isolates resistant to erythromycin and clindamycin, respectively. Three iGAS isolates from 2023 underwent genome sequencing, which indicated that two isolates were emm12 and one was emm28. Phylogenetic analysis showed that the two emm12 isolates were assigned to clade II and closely related to Chinese scarlet fever-causing isolates. The emm28 isolate was assigned to subclades of SC1A and discovered to possess a novel ICE (designated as ICE-SHemm28; Tn916-like) that carried both the ermB gene and the type IV secretion system. Conclusions: Emergence of an emm28 iGAS strain harboring a novel macrolide resistance-carrying type IV secretion system ICE was identified in invasive infections in Shanghai.